Differential Item Functioning of an Academic Stress Scale Among Generation Z Students in Indonesian Islamic Higher Education: A Rasch Rating Scale Model Analysis - Ristianti, Dina Hajja; Sofyan, Afriyadi; Warsah, Idi (Islamic Guidance and Counseling Journal, 2026)
This study evaluated the psychometric properties and measurement fairness of a 25-item academic stress scale among Generation Z undergraduate students at three Indonesian Islamic higher education institutions. Using a cross-sectional design with a final analytical sample of 401 participants (after person-fit screening from an initial N = 517), data were analyzed using the Rasch Rating Scale Model (RSM) to assess rating scale category functioning, item fit, person–item targeting, reliability, and Differential Item Functioning (DIF) across sex, age group, semester, and current living arrangement. Andrich thresholds advanced monotonically (−1.07, −0.79, 0.61, 1.25 logits), confirming that all five response categories represent psychometrically distinct levels of academic stress. Of 25 items, 21 demonstrated acceptable fit; the four misfitting items were concentrated in the Social and Academic Support dimension, consistent with the context-sensitivity of support perceptions in Islamic educational settings. Scale reliability was adequate for group-level research (person reliability = .85; item reliability = .98; Cronbach's α = .88; person separation = 2.41), and person–item targeting was satisfactory (person mean = 0.33 logits). DIF analysis identified seven items with significant sex-based non-equivalence, 17 and 16 items with substantive DIF measure ranges across age group and semester, respectively, and two items with residence-based DIF, collectively indicating that academic stress items function differently across demographic subgroups, particularly for institutional help-seeking, family support, anxiety expression, and time management. These findings demonstrate that while the scale possesses adequate psychometric quality for population screening, measurement invariance is partially violated, and raw-score comparisons across subgroups should be interpreted with caution. Academic stress assessment in Indonesian Islamic higher education should integrate demographic and developmental context, including academic stage and spiritual coping resources, to ensure fair and clinically meaningful score interpretation.